2008
DOI: 10.1016/j.febslet.2008.12.030
|View full text |Cite
|
Sign up to set email alerts
|

IL‐1 family in breast cancer: Potential interplay with leptin and other adipocytokines

Abstract: Edited by Masayuki MiyasakaKeywords: IL-1 Leptin Adipocytokine Breast cancer Obesity a b s t r a c t Obesity is associated with an increased risk of breast cancer. interleukin-1 (IL-1), a pro-inflammatory cytokine secreted by adipose tissue, is involved in breast cancer development. There is also convincing evidence that other adipocytokines including leptin not only have a role in haematopoiesis, reproduction and immunity but are also growth factors in cancer. Therefore, IL-1 family and leptin family are adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 88 publications
3
59
0
2
Order By: Relevance
“…However, the tamoxifen-induced increase in IL1b was associated with a concomitant increase in the level of IL1Ra, a natural inhibitor of IL1, to a higher extent than that of IL1b, leading to inactivation of IL1b. This is consistent with the antitumorigenic property of this cytokine that we, and others, have recently described (27,53).…”
Section: Discussionsupporting
confidence: 92%
“…However, the tamoxifen-induced increase in IL1b was associated with a concomitant increase in the level of IL1Ra, a natural inhibitor of IL1, to a higher extent than that of IL1b, leading to inactivation of IL1b. This is consistent with the antitumorigenic property of this cytokine that we, and others, have recently described (27,53).…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have reported that high IL-1b concentration within the tumor microenvironment is associated with a more virulent tumor phenotype and correlates with a higher rate of recurrence (2,35). Moreover in breast cancer patients, it has been shown that high levels of IL-1Ra and low levels of IL-1 at the tumor site is associated with a better prognosis (36) emphasizing the clinical relevance of our results. The cancer cells in our model did produce low levels of extracellular IL-1b.…”
Section: Discussionsupporting
confidence: 71%
“…Nevertheless, in nonneoplastic skin pathologies, several investigators have reported S100A7 induction in response to inflammatory cytokines, including OSM, IL-1, IL-17, IL-20 and IL-22 (Boniface et al, 2005;Gazel et al, 2006;Liang et al, 2006;Wolk et al, 2006;Bando et al, 2007;Boniface et al, 2007;Sa et al, 2007). Each of these cytokines has the capacity to signal, either directly or indirectly, through STAT3, ERK1/2 and PI3K (Heinrich et al, 2003;Pestka et al, 2004;Gaffen, 2008;Perrier et al, 2008). We have shown previously that S100A7 in breast tumors correlates with Akt activation (Emberley et al, 2005) and now show that OSM and IL-6 can induce S100A7 via PI3K, ERK1/2 or STAT3.…”
Section: Inflammatory Cytokines Induce S100a7 Expression In Breast Cellsmentioning
confidence: 99%